Line Hops and Side Hold Rotation Tests Load Both Anterior and Posterior Shoulder: A Biomechanical Study - Margie K Olds; Nicole Lemaster; Kelsey Picha; Cody Walker; Nick Heebner; Tim Uhl (North American Sports Medicine Institute, 2021)
# Background Clinical tests should replicate the stressful positions encountered during sport participation. Evaluating the kinetic and electromyographical demands of clinical tests enables clinicians to choose appropriate tests for specific sports. # Purpose To describe the shoulder forces and muscle activation levels during closed chain functional tests of Line Hops (LH) and Side Hold Rotation (SHR). # Study Design Descriptive biomechanical study # Methods Ten asymptomatic participants were examined in a university laboratory. Two functional tests were evaluated using three-dimensional video analysis and electromyography to measure shoulder forces, moments, and muscular activity levels. # Results SHR produced a peak average posterior translation force of 4.84 N/kg (CI~95~ 4.32-5.36N/kg) and a peak average anterior translational force of 1.57 N/kg (CI~95~ 1.10-2.01N/kg). High levels of serratus anterior (98% maximum voluntary isometric contraction (MVIC) and infraspinatus (52 %MVIC) were recorded during SHR. LH produced a posterior translational force of 4.25 N/kg (CI~95~ 3.44-5.06N/kg). High levels of serratus anterior (105 %MVIC) and infraspinatus (87 %MVIC) were recorded during the push off phase of this activity. # Conclusions LH and SHR placed large posterior translational forces that approached half of a person's bodyweight on shoulder structures. SHR produced an anterior translation force at extremes of horizontal abduction placing approximately 18% of bodyweight on shoulder structures. The LH test required the serratus anterior to provide power to push the upper torso of the ground while both the serratus and the infraspinatus provides scapular and humeral stability, respectively. # Level of Evidence 4: Case series